Communicating effectively - Hybels, Saundra; Weaver, Richard L. 1941- (McGraw-Hill Education, 2015)
"Communicating Effectively, Eleventh Edition, is written for students taking speech communication classes for the first time. The book covers the theory and practice of communication, first by examining the communication process, second by discussing interpersonal communication, third by looking at other forms of communication including group, intercultural, and professional communication. Communication that occurs on the Internet is covered in a new online chapter, "Communication and Technology." The theory and practice of communication is covered, fourth, through a thorough examination of public communication. The overall approach of the book is pragmatic, so that students can not only see but also appreciate the practical application of the ideas, concepts, and theories in their own lives and in the lives of people who are close to them"--Provided by publisher.